Gamification in Child and Adolescent Health: Trends, Applications, and Policy Relevance for Mental Well-Being, Physical Activity, and Nutrition - Alamer, Ahmed S. (International Journal of Child Health and Nutrition, 2025)
Aim: This study presents a bibliometric analysis of the use of gamification in mental health research (GMHR), aiming to provide a comprehensive quantitative evaluation of publication trends, key contributors, collaboration networks, thematic development, and emerging research themes in this field. Methods: Relevant literature was retrieved from the Scopus database and analyzed using bibliometric tools, including VOSviewer and RStudio. The analysis focused on identifying publication outputs, author collaborations, co-word networks, and thematic evolution from 2013 to 2024. Results: A total of 276 documents were identified, with an annual growth rate of 32.98%. The average number of co-authors per document was 4.99, indicating robust collaborative activity, including international partnerships. Leading contributors included Cheng VWS, Hickie IB, and Fleisch E, who are affiliated with prominent research institutions. Key research themes included gamification, mHealth, anxiety, and ADHD. The findings revealed a dynamic and expanding field responding to contemporary societal mental health needs. Conclusion: Gamification is increasingly being integrated into mental health interventions, showing promise in addressing psychological well-being, particularly among children, adolescents, and individuals with ADHD. Interventions utilizing serious games and mobile health apps have been shown to enhance user engagement, adherence, and cognitive outcomes, especially when targeting anxiety and attention disorders. Empirical studies within the most cited GMHR publications demonstrate effectiveness in areas such as cognitive-behavioral therapy (CBT) delivery, biofeedback-based regulation, and emotion recognition training through game mechanics.